Municipal Solid Waste Management Practices in Urban Areas of Bhimdatta Municipality, Nepal - Hamal, Sagar; Jagari, Sangam; Bohara, Ranjani; Bhatt, Bindu; Bhandari, Ekta; Joshi, Siddhant; Bhatt, Janak Raj (Journal of NAST College, 2025)
Effective municipal solid waste (MSW) management is essential for protecting public health, preserving environmental quality, and promoting sustainable urban development—particularly in rapidly urbanizing municipalities like Bhimdatta, Nepal. Despite national policies such as the Solid Waste Management Act (2011), many local governments continue to rely on unsustainable practices such as open dumping and unsegregated waste collection. This study aimed to assess the current status of MSW management in Bhimdatta Municipality by examining key aspects such as waste generation, composition, segregation practices, collection services, transportation methods, final disposal, and resource recovery. A mixed methods approach was employed in Wards 4 and 18, which represent densely populated urban areas. Data were collected through structured questionnaires administered to 30 households, 63 commercial establishments, and 10 institutions, selected with a simple random sampling, key informant interviews with two municipal officials with purposively selected, and extensive field observations. Results revealed that 64.08% of respondents generated <0.5 kg of waste daily, dominated by organic waste (53%), followed by plastics/polythene (16%), and paper/cardboard (12%). Despite high satisfaction with door-to-door collection services, collection rates were high (86.40%), with 90.30% satisfaction, reasonable cost (81.55%), and convenient morning schedules (92.23%) significant gaps existed. 84.47% of respondents lacked waste segregation practices, and 95.14% of waste was transported manually via uncovered vehicles, causing spillage (9.71% occasional, 4.85% frequent). Final disposal relied on open dumping near a riverbank, 20 meters from settlements. Resource recovery efforts were minimal, with only 11.65% recycling plastics and 28.16% practicing composting. The study underscores an urgent need for targeted policies, strict enforcement of existing waste management regulations, and practical interventions—such as public awareness campaigns, infrastructure upgrades, and sustainable disposal technologies—to improve solid waste management practices.